Sea level instantaneous budget for 2003–2015. Issue 2 (15th December 2021) - Mu, Dapeng; Xu, Tianhe; Guan, Meiqian
SUMMARY: Most studies of sea level budget only indicate the stationary causes for the global mean sea level (GMSL) rise over the course of a time span of interest, providing limited information on temporary changes in the GMSL budget. In this contribution, we present an instantaneous budget of the GMSL for the period of 2003–2015, which offers new insights on the time evolution of the GMSL budget. We use a space-state model to compute the instantaneous rates of GMSL and their contributing sources (barystatic and steric contributions), to investigate the causes of the GMSL instantaneous budget, which accounts for and quantifies low-frequency variations in GMSL rise. Combining the barystatic GMSL instantaneous rates (estimated from satellite gravimetry) along with a particular choice of steric GMSL instantaneous rates (inferred from an Argo product) achieves closure of the GMSL instantaneous budget with a standard deviation of 0.4 mm yr −1 . We find that the barystatic GMSL rate is primarily responsible for the striking fluctuations in the GMSL instantaneous rates between 2009 and 2015. For example, over only 20 months (July 2010 to February 2012), the GMSL (barystatic) rate increases from 0.32 (0.71) to 6.12 (4.55) mm yr −1 . These strong fluctuations mainly result from hydrology and mountain glacier mass variations rather than mass loss in ice sheet, for instance, Australia slowed ∼1.2 mm yr −1 equivalent contribution to GMSL rise over the year 2010, which is approximately four times the linear rate of Antarctica mass loss.